If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(4x + -9) = 399 Reorder the terms: -7(-9 + 4x) = 399 (-9 * -7 + 4x * -7) = 399 (63 + -28x) = 399 Solving 63 + -28x = 399 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + -28x = 399 + -63 Combine like terms: 63 + -63 = 0 0 + -28x = 399 + -63 -28x = 399 + -63 Combine like terms: 399 + -63 = 336 -28x = 336 Divide each side by '-28'. x = -12 Simplifying x = -12
| 9ab-7b+8ab+3b= | | 32+2x=14 | | -3x+4(1+x)=-5(x+5)+5 | | C+b-a=180 | | 4(x-3)=3x-(x-2) | | -5x=12y+4y | | 99+-9=54 | | e-2=21 | | -54=3(-7-2n)-3(n+2) | | 32(16n+3)=24n | | 6.23-6.4+1.11=22.7 | | p^3-7p^2+3P-21=0 | | (-3+5i)(9+i)= | | 7-x+3=3x-4-7x | | z^2+1z=3 | | 5(4r-8)=38+7N | | 4-2(x+3)+1=3 | | -3(x-7)-(-4x+5)=-6x+8x | | 6X^3+5x^2-104x-180=0 | | -g=-40 | | 735.95-15.95=12x | | 3(3y+5)-4y=-5 | | (-5x)+(-2)=(-2x)+4 | | 455=3x+1.5x+x | | -c+A+b=180 | | -(-3b-4)=4(3b-8) | | 70+-5x=20 | | 3n-1=n+4+n | | -8i(20i-13)= | | -4(-8x-8)+7(7-2x)=(16+19x) | | 5x+8x-2x-5=6 | | 9+5=4t |